2021
DOI: 10.1177/23814683211058663
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Decisional Conflict With Measures of Numeracy and Optimism in a Stated Preference Survey

Abstract: Objectives Low optimism and low numeracy are associated with difficulty or lack of participation in making treatment-related health care decisions. We investigated whether low optimism and low self-reported numeracy scores could help uncover evidence of decisional conflict in a discrete-choice experiment (DCE). Methods Preferences for a treatment to delay type 1 diabetes were elicited using a DCE among 1501 parents in the United States. Respondents chose between two hypothetical treatments or they could choose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Third, the preference for current therapy by those with lower educational attainment could be influenced by current therapy being the opt-out alternative in this DCE; indeed, past evidence on DCE design has shown that choosing to opt-out is associated with lower educational attainment [ 20 ]. Finally, decisional conflict, defined as uncertainty experienced when making treatment-related medical decisions, is more common for those with lower educational attainment, and this conflict is also associated with greater likelihood of choosing the opt-out option in DCEs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, the preference for current therapy by those with lower educational attainment could be influenced by current therapy being the opt-out alternative in this DCE; indeed, past evidence on DCE design has shown that choosing to opt-out is associated with lower educational attainment [ 20 ]. Finally, decisional conflict, defined as uncertainty experienced when making treatment-related medical decisions, is more common for those with lower educational attainment, and this conflict is also associated with greater likelihood of choosing the opt-out option in DCEs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%